Efektivitas Penggunaan Media Sosial Instagram Dalam Meningkatkanlayanan Informasi Pada Kantor Imigrasi Kelas I TPI Padang - Vovi Novela (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2024)
This research aims to evaluate the effectiveness of using instagram social media in improving information services at the Padang Immigration Office. The research result show that the use of instagram as a communication and information medium has a positive impact on conveying information to the public. The speed of response, ease of access to information, and interaction between immigration authorities and the community have increased significantly. apart from that, instagram also helps increase transparency and public trust in the services provided. In coclusion, instagram social media is effectively used as a tool to improve the quality of information services at the Padang Immigration Office.